Kesiapan Desa dalam Penerapan E-Government (Studi Perbandingan di Desa Semaya dan Desa Pegiringan Kabupaten Pemalang) - Subhan Subhan; Arif Budy Pratama (Program Studi Administrasi Negara Universitas Serang Raya, 2019)
Many government organizations have implemented e-government. The use of information and communication technology in governments business process spreads only in the central and local government but also in the village level. One of the most important issues in e-government implementation is institutional readiness. This paper aims to examine village government readiness through comparative analysis. The study is located in the Pemalang regency, one of the most active regencies in developing e-government in the village level. Semaya and Pegiringan Village was chosen as research loci since they represented successful and un-succesful outcome of e-government initiatives. To address the research objective, a case study was conducted. The data was drawn from in-depth interview, observation on website and business process, and relevant documents. We find that e-government readiness in the village level can be assessed from the following aspects: data system, regulatory framework, institutional arrangement, human resources, technological infrastructure, and strategic thinking of leadership. Some policy implications can be drawn to improve the e-government readiness in village level.